Biocompatibility of a chlorhexidine local delivery system in a subcutaneous mouse model - Monteiro, Adriana-Socorro-Ferreira [UNESP]; Macedo, Luis-Guilherme-Scavone [UNESP]; Macedo, Nelson-Luiz [UNESP]; Feitosa, Fernanda-Alves; Toyoshima, Thiago [UNESP] (Medicina Oral S L, 2011)
Objective: This study aimed evaluating histologically and histomorphometrically the response of the conjunctive tissue face to the implant of chlorhexidine chips in the subcutaneous tissues of rats. Study Design: In this research 35 male rats Wistar were used to analyze the biocompatibility and the degradation process of chlorhexidine chip. In each animal, it was made 2 incisions for subcutaneous implantation of chlorhexidine chip (test group) and a polytetrafluorethylene membrane (control group). The morphological changes in subcutaneous implantations were assessed after 1, 3, 5, 7, 10, 14, 21 days. The data were submitted to Friedman nonparametric test to analyze the comparisons among observation periods and to allow the comparison among groups. Results: Differences were found in the analysis of the inflammatory response when comparing the tested materials (p values <= 0.05). In test group was observed hemorrhage, edema and intense inflammatory infiltrate predominantly neutrophilic around material. From 3-day and subsequent periods was verified granulation tissue externally at this infiltrate. From 10-day on was observed crescent area of degradation of chlorhexidine chip, associated with neutrophilic and macrophagic infiltrate, that maintained until 21-day. In the control group, moderate inflammatory infiltrate was observed initially, predominantly polymorphonuclear, edema and granulation tissue 3-day period. The inflammatory infiltrate was gradually replaced for granulation tissue, culminating in a fibrous capsule. Giant multinucleate cells situated at contact interface with the coating was examined since 3-day and persisted until 21-day. Conclusion: The chlorhexidine chip induces an intense acute inflammatory response at subcutaneous tissue of rats. Therefore, at conditions of this study was not biocompatible.
Keywords: Biocompatibility; chlorhexidine toxicity; drug delivery system; periodontitis